2011
DOI: 10.1177/0363546511430375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results and Risk Factors for Reinjury 15 Years After Anterior Cruciate Ligament Reconstruction

Abstract: Anterior cruciate ligament reconstruction using ipsilateral autograft continues to show excellent results in terms of patient satisfaction, symptoms, function, activity level, and stability. The use of HT autograft does, however, show better outcomes than the PT autograft in all of these outcome measures. Additionally, at 15 years, the HT graft-reconstructed ACLs have shown a lower rate of radiological osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
254
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(290 citation statements)
references
References 31 publications
28
254
0
5
Order By: Relevance
“…One point six percent of patients needed revision ACL reconstruction but a total of 33% needed further knee surgery during follow-up. Leys et al [25] who compared HS to BTPB showed in the BTPB arm of their study that there was no significant difference to HS in overall IKDC grade, whereas radiographic evidence of osteoarthritis was significantly more common in BPTB. Ahn et al [33] looked at 117 patients with mean 10.3 year follow-up after BTPB reconstruction and showed 90.6% normal or nearly normal IKDC subjective scores.…”
Section: Graft Choicementioning
confidence: 95%
See 1 more Smart Citation
“…One point six percent of patients needed revision ACL reconstruction but a total of 33% needed further knee surgery during follow-up. Leys et al [25] who compared HS to BTPB showed in the BTPB arm of their study that there was no significant difference to HS in overall IKDC grade, whereas radiographic evidence of osteoarthritis was significantly more common in BPTB. Ahn et al [33] looked at 117 patients with mean 10.3 year follow-up after BTPB reconstruction and showed 90.6% normal or nearly normal IKDC subjective scores.…”
Section: Graft Choicementioning
confidence: 95%
“…Other studies of HS tendons with similar follow-up are uncommon. Leys et al [25] reported results from a cohort study with 15 years follow-up comparing HS to BPTB. In the HS arm they had 15 year results on 51 patients.…”
Section: Graft Choicementioning
confidence: 99%
“…ACL graft re-rupture rates range from 1.8% to 25% and the rate of contralateral ACL injury ranges from 3% to 26% [94,119,166,167,171,189,229,236,239] depending on follow-up time (2-15 years), age and activity level in the population. Several of the studies reported a higher incidence for contralateral ACL injuries than sustaining an ACL graft rupture [94,119,166,167,171,229,239]. Most new ACL inju-ries occurred in the first 2-3 years after ACLR, and the ACL graft ruptures typically occurred earlier than contralateral ACL injuries [189,194].…”
Section: Epidemiology and Aetiology Of An Additional Acl Injurymentioning
confidence: 99%
“…After ACLR, males tend to sustain more ACL graft ruptures [28,94,119,127] and females tend to sustain more contralateral ACL injuries [127,165,166,194]. In a systematic review and meta-analysis of the importance of patient sex in the outcome of ACLR, females had a higher revision rate (relative risk, 1.15; 95% CI, 1.02-1.28), but graft rupture (33 studies included) or failure (18 studies included) did not differ compared with males.…”
Section: Epidemiology and Aetiology Of An Additional Acl Injurymentioning
confidence: 99%
See 1 more Smart Citation